Retailing to Women Requires a Holistic Approach - Srinivas, T.; Kishore Babu, M. (Indian Journal of Marketing, 2008)
Retailing to women seems so complicated due to their purchase decision-making paths, which are bit winding. The key to understanding how to reach women buyers understands how women buyers think. Remember when women used to be viewed as a homogenous "minority" consumer segment? That time has certainly come and gone, as evidenced by the many that car manufacturers, hardware stores, banks and cosmetic retailers, among others, have been putting into more narrowly focused, segment-specific campaigns. Even olden days had witnessed exclusive goods dispensing and retailing to women of Rajputs, Muslim and wives of merchants&select communities. Yet single women remain one of the most neglected consumer groups.Sixty per cent of India is below 30 years of age, and has equal presence of young women those will earn and consume a lot. As per estimates to day, women control 80% of family purchases. At same time retailers are making attempts to develop formats to target women in particular. Women differ from men on various parameters such as physicality, psychographics, behavioral parameters and consumption. According to a MasterCard's Asian Lifestyles Survey conducted recently in 13 Asian countries including India, almost 80% of women consider travel important for their lifestyles. It further states that these cosmopolitan women travelers are highly educated tech savvy, posses' high disposable income and increasingly adventurous experiences. Six keys will help companies get into the retailing to women mindset: Narrow your focus; understand your customer community intimately; Build customer feedback into the process; Focus on your product's context; Understand and define brand; be authentic.. Women no longer remain as niche market or as an exclusive market segment; rather they have emerged as major buyers of all kinds of products.